2005
DOI: 10.1038/nn1402
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of telencephalic precursors from embryonic stem cells

Abstract: We demonstrate directed differentiation of telencephalic precursors from mouse embryonic stem (ES) cells using optimized serum-free suspension culture (SFEB culture). Treatment with Wnt and Nodal antagonists (Dkk1 and LeftyA) during the first 5 d of SFEB culture causes nearly selective neural differentiation in ES cells ( approximately 90%). In the presence of Dkk1, with or without LeftyA, SFEB induces efficient generation ( approximately 35%) of cells expressing telencephalic marker Bf1. Wnt3a treatment durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
639
9
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 730 publications
(683 citation statements)
references
References 47 publications
33
639
9
2
Order By: Relevance
“…Consistently, BMP signaling inhibits neural induction and stimulates the formation of the epidermis from mouse ES cells [62][63][64]. Moreover, activation of Nodal signals suppresses neural differentiation from mouse ES cells [65]. Together, these findings indicate that TGF-β family signaling inhibits the commitment of ES cells to neuroectoderm.…”
Section: Ectoderm Derivativesmentioning
confidence: 78%
“…Consistently, BMP signaling inhibits neural induction and stimulates the formation of the epidermis from mouse ES cells [62][63][64]. Moreover, activation of Nodal signals suppresses neural differentiation from mouse ES cells [65]. Together, these findings indicate that TGF-β family signaling inhibits the commitment of ES cells to neuroectoderm.…”
Section: Ectoderm Derivativesmentioning
confidence: 78%
“…The identification of the regulatory networks controlling these sequential events has recently benefited from studies highlighting the similarities between the precursors present in the embryo and the in vitro cell types obtained in neural differentiation protocols of stem cells (IwafuchiDoi et al, 2012;Lupo et al, 2014). In vivo and in vitro evidence has demonstrated that inhibition of NODAL/ACTIVIN signalling promotes neural fate acquisition in the mouse embryo, as well as during differentiation of mESCs, mouse epiblast stem cells (mEpiSC), and hESCs (Camus et al, 2006;Chng et al, 2010;Li et al, 2013;Patani et al, 2009;Smith et al, 2008;Turner et al, 2014;Vallier et al, 2009;Watanabe et al, 2005). It is tempting to extrapolate that the attenuation of NODAL signalling observed in N1ICD epi embryos from E6.5 contributes to the premature expression of Sox1 in the distal anterior epiblast of these embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Within the differentially expressed genes, AP2γ was found to be markedly upregulated by BMP4 at both mRNA and protein levels (Supplementary information, Figure S1). ESC neural differentiation in knockout serum replacement (KSR) medium was used as an in vitro model [38,39] to study AP2γ function in early embryonic development. We found that AP2γ mRNA was expressed in undifferentiated mouse ESCs and that its level gradually decreased with progressing neural conversion ( Figure 1A), suggesting that AP2γ might be involved in the neural differentiation of ESCs.…”
Section: Ap2γ Knockdown Facilitates Neural Differentiation and Impairmentioning
confidence: 99%